Experimental study on the seismic performance of precast concrete columns with thread-bolt combination couplers. (15th January 2022) - Qing, Yuan; Wang, Chun-Lin; Meng, Shaoping; Zeng, Bin
Highlights: Proposing precast columns using couplers with the threaded connection and bolt fastening. Conducting quasi-static tests to investigate the behaviors of the precast columns. Proposing a simplified method to evaluate the deformation capacity of precast columns. Abstract: A new precast concrete column system was proposed in this paper to reduce the demands of threaded couplers on the manufacturing errors of precast members and to satisfy the design philosophy of demountable and recyclable concrete members. In the precast system, a novel coupler (CTB coupler) with a combination of threaded connection and bolt fastening was adopted to provide the longitudinal rebar of the column with continuity. The CTB coupler was connected with the upper and lower rebar by threaded connection and bolt fastening, respectively. A quasi-static test was performed for two monolithic concrete columns and three precast columns with CTB couplers (CTB column) to investigate the hysteretic performance of the CTB column. The experimental results illustrated that the CTB columns exhibited an ultimate drift ratio of more than 1/50, a ductility factor of greater than 3.48, and a greater bearing capacity than monolithic concrete columns. The above results validated the reliability of the CTB coupler. Eventually, a simplified model was proposed to calculate the ultimate drift ratio of the CTB column. The calculated value of the CTB column matched well with its measured value, with the ratios of the values ranging from 0.97 to 1.03.